Monetary integration and dollarization : no panacea - Vernengo, Matias (Northampton, MA : Edward Elgar, 2006)
This book brings together an impresive and diverse group of authors to discuss its central:whether or not the dollarized international monetary system is sustainable in the context of the global economy it helped create.
Includes bibliographical references and index.
aug 06/06/13
Loans
Keywords: Dollarization; Currency question; Foreign exchange; Monetary policy; Dollar, American; Europe; Developing countries